THE SOLITUDE OF THE STANCE: THE BODILY AUTOLOGY OF GYM-WORK AND BOXING IN AN ESSEX TOWN - Lockwood, Peter (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2016)
Contemporary accounts of masculinity in Britain have tended to focus on the politics of body image: how and why young men aspire to appear a certain way through forms of body modification. Drawing on ethnography carried out amongst young British males in Essex, this paper homes in on the technical processes of body modification itself, arguing that what is at stake in practices such as working out at the gym is not only the transformation of appearance. Rather than seeing practices such as weight-lifting as failed acts of resistance, where men attempt to craft themselves as physically powerful individuals while ultimately conforming to gender stereotypes and norms, what follows is an argument that posits the body as a locus of sensory self-enunciation. Drawing upon the praxeological method of Jean-Pierre Warnier, I advance a sensorylogical analysis of weight-lifting practices to show how young men quite literally embody themselves as capable and agentive persons. I further explore these questions of embodied self-enunciation at the Billericay Boxing Hut where I analyse forms and logics of sensory experience that allow men to render themselves persons defined by the capacity to overcome pain from within. I argue that boxing training and weight-lifting in the gym instantiate a local principle of male personhood, autology: the sense young men have of being individual, self-determining and agentive persons. Gym-work and boxing are thus re-interpreted as acts of bodily autology: practical acts that elicit a singular and capable self.